Qualitätssicherung Invasive Kardiologie – 7. Bericht des Bundesverbandes Niedergelassener Kardiologen zur Qualitätssicherung in der diagnostischen und therapeutischen Invasivkardiologie 2010-2012 - Levenson, B.; Albrecht, A.; Göhring, S.; Haerer, W.; Reifart, N.; Ringwald, G.; Schräder, R.; Troger, B. (Aktuelle Kardiologie, 2013)
On behalf of the German Association of Cardiologists in Private Practice (BNK) the Steering Committee of the QuIK Registry reports the results 2010 to 2012 of the voluntary Quality Assurance in Invasive Cardiology (QuIK) and compares them to other data collections. More than 70 % of diagnostic (LHC) and therapeutic (PCI) cardiac catheterization procedures in private practice were entered into the registry. Altogether 225,756 LHC and 63,951 PCI were documented over the three years period. In these years age of patients and percentage of acute coronary syndromes increased as well in LHC as in PCI while consumption of dye solution and application of radiation dose decreased. In PCI the rate of 3-vessel coronary artery disease is still continuously rising. These parameters prove the increasing complexity of the cases. By implemented standardized external auditing (monitoring) to guarantee validity of the data QuIK remains a worldwide unique quality assurance project in cardiology. On a stable data base over all together 17 years the QuIK Registry shows the reality of every day cardiologic care in catheterization laboratories beyond selected study populations as well as a reliable feasibility of internal and external quality assurance.